2016
DOI: 10.1111/are.13121
|View full text |Cite
|
Sign up to set email alerts
|

Tank size and fish management history matters in experimental design

Abstract: To investigate the questions: (1) does tank size affect fish performance; (2) does tank size prior to an experiment affect later fish performance and (3) how does performance in experimental tanks compare with rearing in industry-scale cages, Atlantic salmon smolts were acclimatized to 190, 3 or 0.9 m 3 tanks (Phase 1; 1.5 months) before redistributed to Phase 2 for 5 months. Question 1: fish in 190 m 3 tank were redistributed to 0.9 m 3 (190 m 3 ? 0.9 m 3 ), 3 m 3 (190 m 3 ? 3 m 3 ), or 103 m 3 (190 m 3 ? 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…The experiments conducted by Espmark et al (in press) illustrated how differences in physical scale (i.e. geometric size) or scaling histories will affect Atlantic salmon performance in indoor tank facilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments conducted by Espmark et al (in press) illustrated how differences in physical scale (i.e. geometric size) or scaling histories will affect Atlantic salmon performance in indoor tank facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have found that the growth of Atlantic salmon may be affected by factors such as tank size and current speed ( Boeuf and Gaignon, 1989 ), and fish density ( Refstie and Kittelsen, 1976 ), which are all relevant elements when considering scaling effects. ( Espmark et al, in press ) focused on assessing this question more directly by conducting an experiment where a set of land based tanks of different geometric sizes (0.9, 3, 103 and 190 m 3 ) were stocked with Atlantic salmon smolts from a common genetic strain and cohort. The main aim of that study was to investigate whether there were differences in fish performance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to experiments in sea cages, a tank experiment has the advantages that spreading of feed, feed intake and growth can be measured with high accuracy, and it can be run at a relatively low cost. Data from small scale studies are not necessarily valid for large scale conditions (Espmark et al, 2017). As for all trials, the data from the present study are only representative for the conditions used in this study.…”
Section: Discussionmentioning
confidence: 84%
“…In tanks, the behavior is restricted by the volume of the tank. Volume and design of the tanks have been shown to affect feed intake and growth in salmon (Espmark et al, 2017;Føre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We considered this experimental set-up to be not only more industry relevant but also necessary to ensure the welfare of the animals over the 24-week experimental period. Recently, Espmark et al (2017) highlighted the negative effects of keeping fish in smaller tanks, i.e., reduced food intake and growth. Once allocated, the temperature in each tank was adjusted over 72 h to one of three temperatures: 4, 8, and 12 • C (two tanks per temperature) and maintained in a flowthrough system at those temperatures, using an inbuilt heat exchange panel for the duration of the trial.…”
Section: Animal Husbandry and Experimental Conditionsmentioning
confidence: 99%